Down‐regulated miR‐26a promotes proliferation, migration, and invasion via negative regulation of MTDH in esophageal squamous cell carcinoma. Issue 5 (7th February 2017) - Yang, Chenchen; Zheng, Shutao; Liu, Tao; Liu, Qing; Dai, Fang; Zhou, Jian; Chen, Yumei; Sheyhidin, Ilyar; Lu, Xiaomei
ABSTRACT: Numerous studies have reported that the role played by miR‐26a in cancer is controversial, but whether miR26a regulates metadherin (MTDH) expression in esophageal squamous cell carcinoma (ESCC) is unclear. We performed this study to investigate the clinical relevance of miR‐26a expression in ESCC. miR‐26a was detected by using the in situ hybridization method. To functionally analyze the role of miR‐26a in ESCC cell lines in vitro, KYSE‐450 and Eca109 cells were employed, whose endogenous miR‐26a was artificially down‐ or up‐regulated, respectively, by using lentiviral‐based transfection. There was significant association between miR‐26a expression and clinical stage (P = 0.049), lymph node metastasis (P = 0.023), tumor volume (P = 0.003), and poor overall prognosis (P = 0.026). miR‐26a was able to suppress proliferation and migration of ESCC cells in vitro. Moreover, we have confirmed that miR‐26a can negatively regulate MTDH in ESCC cells by using luciferase reporter assay. In addition, to investigate the role miR‐26a plays in cell proliferation, we nude mice were xenografted with ESCC cells whose miR‐26a was stably down‐ and up‐regulated. Together, our results show that miR‐26a is capable of suppressing the proliferation and migration of ESCC cells via negative regulation of MTDH. Moreover, miR‐26a expression was clinically relevant in cancer progression and poor prognosis, which supports the idea that miR‐26a acts as a tumor suppressor in ESCC.—Yang, C., Zheng, S., Liu, T., Liu, Q., Dai, F., Zhou, J., Chen, Y., Sheyhidin, I., Lu, X. Down‐regulated miR‐26a promotes proliferation, migration, and invasion via negative regulation of MTDH in esophageal squamous cell carcinoma. FASEB J. 31, 2114–2122 (2017). www.fasebj.org